EKOEFISIENSI, BIAYA LINGKUNGAN, DAN CORPORATE SOCIAL RESPONSIBILITY PADA KINERJA KEUANGAN - Elida Mardiana; Zul Azmi; Muhammad Ahyaruddin (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This research tends to determine the influence of eco-efficiency, corporate social responsibility, and environmental costs on the financial performance of manufacturing companies listed on the IDX in 2021-2022. The research’s population are manufacturing companies listed on the IDX in 2021-2022. The type of data employed in this research is quantitative data. Study was established on the IDX’s official website using secondary data. The sampling method employed was the purposive sampling technique. The sample on this research was 212 companies. The data analysis method employed is multiple linear regression and tested using the t test. Research results show that eco-efficiency, corporate social responsibility, and environmental costs have a significant influence on the manufacturing companies; financial performance that listed on the IDX in 2021-2022.